Toward a Systematic Evaluation of Usability in RESTful APIs: A Metric-Based Approach - Machini, Ariel (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
In recent years, web APIs have become a crucial part of modern software development, as they allow easy access to a wide variety of resources and services. This has led to a competitive market, “the API economy”, and as a consequence, usability now plays a key role in the success of web APIs. Despite that, usability is often overlooked because there is no standard way to measure the usability of a web API. This work aims to address this problem by proposing a comprehensive model that enables systematic assessment of web API usability from various perspectives.